Radiopharmaceutical Chemistry between Imaging and Endoradiotherapy Radiopharmaceutical Chemistry between Imaging and Radioendotherapy (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Positron emission tomography (PET), single photon emission computed tomography (SPECT), and the combined imaging modalities realised in the en-vogue hybrid technologies PET/CT and PET/MR represent the state-of-the-art diagnostic imaging technologies in nuclear medicine which are used for the highly sensitive non-invasive imaging of biological processes at the subcellular and molecular level in a respective patient for the visualisation of rather early disease states or for early inspection of treatment response after chemotherapy, radiation- or radioendotherapy. Radiolabelled molecules, bearing a "radioactive lantern", function as so called Radiopharmaceuticals which have to be compliant with the pharmaceuticals act, and can be termed as "food" of nuclear medicine. In general, the specialised field Radiopharmaceutical Chemistry focusses on the development, synthesis and radiolabelling of aforementioned "food", such as small molecules, biotechnology-derived antibodies or (cyclised) (oligo)peptides which are used to address clinically relevant biological "downstream" targets such as receptors, enzymes, transport systems and others. Addressing "upstream" targets such as DNA- and RNA-fragments using corresponding radioactive substrates represents a further feasible strategy. Originally, Radiopharmaceutical Chemistry descends from radiochemistry and radiopharmacy as well as nuclear chemistry and uses methods finally aiming at the production of radioactive substances for human application which are essential for non-invasive in vivo imaging by means of the aforementioned scintigraphic methods PET or SPECT. The cornerstone for applicable radiochemistry in nuclear medicine was set by the Hungarian chemist George Charles de Hevesy who received the Nobel Prize in 1943 for his work on the radioindicator principle. This principle is based on the idea that the absolute amount of the administered substance is below the dose needed to induce a pharmacodynamic effect. Nowadays, a radioactive substance that can be traced in vivo as it moves through the living organism is termed radiotracer or radiopharmaceutical. As mentioned above, the biodistribution of radiopharmaceuticals is measured non-invasively reflecting functional or molecular disorders without pharmacologically affecting the organism. In the era of personalised medicine the diagnostic potential of radiopharmaceuticals is directly linked to a subsequent individual therapeutic approach called radioendotherapy. Depending on the "radioactive lantern" (gamma or particle emitter) used for radiolabelling of the respective tracer molecule, the field Radiopharmaceutical Chemistry can contribute to the set-up of an in vivo "theranostic" approach especially in tumour patients by offering tailor-made (radio)chemical entities labelled either with a diagnostic or a therapeutic radionuclide. To succeed in the design of targeted high-affinity radiopharmaceuticals that can measure the alteration of receptors serving at the same time as biological targets for individualised radioendotherapy several aspects need to be considered: (i) reasonable pharmacological behaviour (especially pharmacokinetics adjusted to the physical half-life of the used radionuclide), (ii) ability to penetrate and cross biological membranes, (iii) usage of chemical as well as biological amplification strategies (e.g. pretargeting, biological trapping of converted ligands, change of the physicochemical behaviour of the radiopharmaceutical after target interaction, combination with biotransporters and heterodimer approaches), (iv) availability of radiopharmaceuticals with high specific activities and in vivo stability.